Augmenting regulatory T cells: new therapeutic strategy for rheumatoid arthritis - Zhang, Jiaqian; Liu, Hongjiang; Chen, Yuehong; Liu, Huan; Zhang, Shengxiao; Yin, Geng; Xie, Qibing (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune condition marked by inflammation of the joints, degradation of the articular cartilage, and bone resorption. Recent studies found the absolute and relative decreases in circulating regulatory T cells (Tregs) in RA patients. Tregs are a unique type of cells exhibiting immunosuppressive functions, known for expressing the Foxp3 gene. They are instrumental in maintaining immunological tolerance and preventing autoimmunity. Increasing the absolute number and/or enhancing the function of Tregs are effective strategies for treating RA. This article reviews the studies on the mechanisms and targeted therapies related to Tregs in RA, with a view to provide better ideas for the treatment of RA.